Apuntes para una reflexión acerca de la educación superior en Colombia. Retos y perspectivas. (2021)
The present paper tries to present a general panorama of the higher education in Colombia nowadays, trying to define certain conditions of change that have been given for this referring and to consider some of the challenges and projections that from the reality of the author the institutions must confront , in the perspective that this process implies. This writing must be understood only as a first approach to comprehend the reality of the higher education in the country and the role the university plays in the transformation of the dynamics of change that the educational system faces at the moment. Therefore, this document more than making a diagnosis about the situation of the higher education in Colombia ( where some statistical referring and in general quantitative referrings are shown ) , what it wants is to show trough a general reflection, a global panorama about the higher education in the country and to determine the importance that for the universities and the state hast to reflect on aspects like internationalization, flexibility, investigation and evaluation as the main challenges that the actors who are compromised with the process must face.